Glocalizing creative hub concept for Malaysian creative city development: a conceptual review - Khoo, Suet Leng; Lim, Yoke Mui; Nurwati Badarulzaman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The creative hub concept is gaining popularity globally as a tool within the creative economy to generate socio-economic and cultural values for societal and community development. Though the concept is nascent and the creative hub itself can be manifested in variegated forms, the notion is oftentimes linked to urban development particularly the way creative hubs are found to be subsumed and contribute towards the growth of creative industries en route the formation of a creative city. Against this backdrop, this paper aims to explore the creative hub concept and the way this global concept it is being understood, adopted and adapted locally amidst Malaysian local nuances. Based on secondary data sources, a systematic literature review was conducted to review global definitions, concepts, examples and illustrate how creative hubs are linked to creative city development and sustainable urban development. Literature review based on similar themes for the Malaysian context showed that the creative hub concept is also variegated, and each hub is shaped by the initiators, funding model and formation purpose of either commercial, social or culture and artistic. The paper concludes that reconceptualization of Malaysian creative hubs is timely and apt by taking into consideration also elements like location, culture-specificity and the influence of ICT as the creative hub concept, its form and operations morph and navigate in response to the current global COVID-19 pandemic. The implications that derive from this study will have conceptual, practical and policy implications when adopting and adapting the creative hub concept for the Malaysian context.